Survey on e-health knowledge and usage in general cardiology of the Council of Cardiology Practice and the Digital Health Committee. Issue 2 (7th April 2021) - Asteggiano, Riccardo; Cowie, Martin R; Richter, Dimitrios; Christodorescu, Ruxandra; Guasti, Luigina; Ferrini, Marc
Abstract: The Council for Cardiology Practice of the European Society of Cardiology (ESC), in collaboration with the Digital Health Committee (DHC), undertook an electronic survey with 15 question multiple-choice questionnaire sent to 32 461 members of the ESC with the aim to assess the knowledge and usage of digital health (DH) technologies (DHTs) by office-based cardiologists. Of 559 respondents, 57% graded their knowledge about DH as 'fair' and three quarters identified the correct definition of DH. Clinical information systems, mHealth Apps, and telemedicine were the most frequently used DHTs, but 41% of respondents had concerns about their ethical and data transparency. Lack of legal clarity, low patient motivation, limited DH literacy, and poor access to DH were perceived as the main barriers to the adoption of DH. Seventy percent of the respondents were aware of the DH pages on the ESC website and 76% of the educational sessions in the DH area during the ESC Congress 2019. Only 16% had not read articles on DH. Eight-eight percent of responders declared that they would 'probably' or definitely attend future educational initiatives on DHT. Graphical Abstract: